Amplifying Lewis acidity by oxidation: leveraging the redox-activity of bis(3,6-di-tert-butyl-catecholato)silane - Thorwart, Thaddäus; Schmitt, Manuel; Greb, Lutz (Dalton transactions, 2025)
Bis(catecholato)silanes were showcased as strong Lewis acids, while their inherent redox activity remained unexplored in this context. In the present work, we study the oxidation of monomeric bis(3,6-di-tert-butyl-catecholato)silane (1), leading to the Lewis superacidic radicalic silylium ionradical 1˙+ (FIA 784 kJ mol−1). Oxidation of 1 with [N(p-C6H4Br)3][B(C6F5)4] yielded [1][B(C6F5)4], displaying strong catalytic activity in the Friedel-Crafts-dimerization, hydrodeoxygenation and carbonyl-olefin-metathesis. It demonstrates how Lewis acidity can be amplified through oxidation without needing an add-on redox-active substituent. Instead, it synergizes the constraining effect of catecholates with their inherent redox non-innocence to unlock enhanced catalytic performance.